The Transport History of Alluvial Fan Sediment Inferred From Multiple Geochronometers. Issue 9 (8th September 2021) - Goehring, Brent M.; Brown, Nathan; Moon, Seulgi; Blisniuk, Kimberly
Abstract: We present a multi‐chronometer approach to refine the age of an alluvial fan and to infer sediment transport and deposition history in the Anza Borrego Desert region of Southern California. We measure in situ produced cosmogenic carbon‐14 ( 14 C) from boulders on the fan surface and infrared stimulated luminescence (IRSL) ages from single feldspar grains within the alluvium. Our new IRSL age [5.3 ± 0.5 ka (±1 σ )] is in excellent agreement with existing uranium‐series [U‐series; 5.3 ± 0.2 (±2 σ )] ages of pedogenic carbonates. The IRSL and U‐series ages show that in situ 14 C measurements [6.6 ± 1.1 ka (±1 σ )] from boulders contain inherited nuclides from prior exposure in the upstream catchment, much like measurements of the longer‐lived nuclide, beryllium‐10 ( 10 Be). However, in situ 14 C ages are closer to the preferred ages inferred from IRSL and U‐series and with less scatter than comparative 10 Be ages. Our data demonstrate that a multi‐geochronometer approach will produce ages of alluvial fan surfaces with the greatest degree of confidence. We then apply the paired 14 C and 10 Be concentrations to infer the prior exposure and storage duration of the sampled boulders of 3.1 ± 3.2 and 4.6 ± 2.3 Kyr, respectively. A mixture model analysis of the single grain IRSL ages suggests bimodal storage durations prior to remobilization with peaks at ca. 2 and 10 Kyr. We demonstrate that cosmogenic nuclide inheritance and single grain IRSL equivalent dose distributions can provide additional information regarding sediment transport history prior to deposition on the alluvial fan. Plain Language Summary: Alluvial fans are the accumulations of sediments stored at the base of mountains. Sediment accumulates via mechanisms that are episodic in nature. Often sediment is stored in the upstream watershed for periods of time before being delivered to the base of the mountain as an alluvial fan, where it is deposited and subsequently buried by younger fan deposits. The ability to date alluvial fan surfaces and subsurface deposits has profound implications for the use of alluvial fans as climate archives and to determine slip rates along faults that offset alluvial fan surfaces. We present measurements of the cosmogenic nuclides carbon‐14 and beryllium‐10 from boulders from an alluvial fan surface in the Anza Borrego Desert of Southern California, USA, along with measurements of post‐infrared infrared luminescence from sands that underlie the same fan surface. Our results show that the luminescence data appear to yield robust ages for sediment accumulation in the fan. The cosmogenic nuclides data is not directly applicable to fan surface age determination. We further show that combining the two geochronometers also yields information about sediment storage in the upstream watershed and that in some cases, sediment can be stored for a longer period of time. Key Points: In situ cosmogenic carbon‐14 from alluvial fan surfaces can have inheritance regardless of its short half life Infrared stimulated luminescence chronology appears to be a robust alluvial fan chronometer Geochronometric information can be inverted for sediment history in a catchment upstream of an alluvial fan